The mechanics of congenital heart disease: from a morphological trait to the functional echocardiographic evaluation - Avesani, Martina; Sabatino, Jolanda; Borrelli, Nunzia; Cattapan, Irene; Leo, Isabella; Pelaia, Giulia; Moscatelli, Sara; Bianco, Francesco; Bassareo, PierPaolo; Martino, Francesco; Leonardi, Benedetta; Oreto, Lilia; et al. (Frontiers in Cardiovascular Medicine, 2024)
Advances in pediatric cardiac surgery have resulted in a recent growing epidemic of children and young adults with congenital heart diseases (CHDs). In these patients, congenital defects themselves, surgical operations and remaining lesions may alter cardiac anatomy and impact the mechanical performance of both ventricles. Cardiac function significantly influences outcomes in CHDs, necessitating regular patient follow-up to detect clinical changes and relevant risk factors. Echocardiography remains the primary imaging method for CHDs, but clinicians must understand patients' unique anatomies as different CHDs exhibit distinct anatomical characteristics affecting cardiac mechanics. Additionally, the use of myocardial deformation imaging and 3D echocardiography has gained popularity for enhanced assessment of cardiac function and anatomy. This paper discusses the role of echocardiography in evaluating cardiac mechanics in most significant CHDs, particularly its ability to accommodate and interpret the inherent anatomical substrate in these conditions.